2017
DOI: 10.1063/1.4977060
|View full text |Cite
|
Sign up to set email alerts
|

Influence of molecular vibrations on the valence electron momentum distributions of adamantane

Abstract: We report an electron momentum spectroscopy study of vibrational effects on the electron momentum distributions of the outer valence orbitals of adamantane (C 10 H 16). The symmetric noncoplanar (e, 2e) experiment has been carried out at an incident electron energy of 1.2 keV. Furthermore, theoretical calculations of the electron momentum distributions with vibrational effects being involved have been performed using the harmonic analytical quantum mechanical and Born-Oppenheimer molecular dynamics approaches.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 74 publications
(103 reference statements)
0
8
0
Order By: Relevance
“…The RAES is presented in the binding energy scale, calculated as the difference between the photon energy and the auger electron kinetic energy. In the RAES, the final states of the adamantane cation [ 29 , 30 ] (grey dashed lines) are assigned using the reference photo-emission spectrum of valence ionization (black) taken at an off-resonance photon energy of 285 eV. Two distinct regions were identified in the RAES, corresponding to participator Auger decay (1h) at the low binding energy (<17.5 eV), and spectatorAuger decay (2h-1p) at the high binding energy (>25 eV).…”
Section: Resultsmentioning
confidence: 99%
“…The RAES is presented in the binding energy scale, calculated as the difference between the photon energy and the auger electron kinetic energy. In the RAES, the final states of the adamantane cation [ 29 , 30 ] (grey dashed lines) are assigned using the reference photo-emission spectrum of valence ionization (black) taken at an off-resonance photon energy of 285 eV. Two distinct regions were identified in the RAES, corresponding to participator Auger decay (1h) at the low binding energy (<17.5 eV), and spectatorAuger decay (2h-1p) at the high binding energy (>25 eV).…”
Section: Resultsmentioning
confidence: 99%
“…Although the equilibrium geometry approximation by eq has been widely used to analyze the experimental data, recent EMS studies have shown that molecular vibration may appreciably affect the momentum profiles of polyatomic molecules. In order to take the vibrational effects into account, we have developed a theoretical method, which is referred to as the harmonic analytical quantum mechanical (HAQM) approach . Details of the approach are given elsewhere and not repeated here.…”
Section: Theoretical Calculationsmentioning
confidence: 99%
“…Distinct discrepancies between the experiments and calculations were observed, especially for the 5b 2 orbital, which is mainly the C–S σ bonding orbital. Numerous factors may lead to the discrepancies, for example the deviation from plane wave impulse approximation (PWIA) (distorted wave effect), relativistic effect, and vibrational effect. …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the equilibrium geometry of the molecule is commonly invoked to calculate theoretical momentum profiles (TMPs) when interpreting EMS results. However, recent investigations have shown that for polyatomic molecules, the nuclear vibrational motions have noticeable influence on EMPs. To fully estimate vibrational effects on EMPs theoretically, Watanabe et al proposed a harmonic analytical quantum mechanical (HAQM) approach, , in which all the vibrational modes were taken into account and the contributions of each mode can be estimated individually.…”
Section: Introductionmentioning
confidence: 99%